Student’s Perceptions of Numeracy Assessment in The Context of Children's Games for STEAM Education in Elementary Schools - Wiryanto Wiryanto; Ika Rahmawati; Suprayitno Suprayitno; Ganes Gunansyah; M. Gita Primaniarta (Al Ibtida: Jurnal Pendidikan Guru MI, 2024)
AbstractStudents' achievement of numeracy competency requires strengthening and modifying game themes that are relevant to daily activity situations. The purpose of this study is to explain the perception of students' numeracy context needs as a process in STEAM education in elementary schools. The research method used is descriptive qualitative through observation, interviews and questionnaires. The subjects of the study were 60 students of SDN Sidotopo Wetan V and SD Kyai Ibrahim Surabaya in 2023. Research data analysis using Miles and Huberman techniques in the form of data collection, data reduction, data explanation and conclusions. The results of this research are answers consisting of 10 questionnaire questions distributed regarding the need for numeracy questions in the context of games. The highest aspect of numeracy needs related to student needs is that numeracy assessment with a game context can attract students' interest and help the learning process with a score of 93.3% each. STEAM education can identify the elements that make up a numeracy problem to help students enjoy the learning content. Numeracy problems related to the fifth aspect of STEAM will fulfil and make it easier to understand the context of the questions by playing games for children. Keywords: numeracy assessments, games, STEAM.                                                              AbstrakCapaian kompetensi numerasi peserta didik memerlukan penguatan serta modifikasi dari tema permainan gim yang relevan situasi aktivitas sehari-hari. Tujuan penelitian ini adalah untuk menjelaskan persepsi kebutuhan konteks numerasi dari peserta didik sebagai proses dalam Pendidikan STEAM di sekolah dasar. Metode penelitian yang digunakan adalah deskriptif kualitatif melalui observasi, wawancara, dan kuesioner. Subjek penelitian dilakukan oleh 60 peserta didik dari SDN Sidotopo Wetan V dan SD Kyai Ibrahim Surabaya tahun 2023. Analisa data penelitian yang digunakan menggunakan teknik miles and huberman berupa pengumpulan data, reduksi data, penjelasan data dan kesimpulan. Hasil penelitian ini merupakan jawaban dari sebaran 10 pertanyaan kuisioner mengenai kebutuhan persoalan numerasi konteks permainan gim. Aspek kebutuhan numerasi tertinggi mengenai kebutuhan peserta didik adalah asesmen numerasi dengan konteks permainan gim dapat membuat tertarik peserta didik dan membantu dalam proses pembelajaran dengan skor masing-masing 93,3%. Pendidikan STEAM dapat mengidentifikasi unsur pembentuk persoalan numerasi membantu peserta didik menyukai konten pembelajaran. Persoalan numerasi yang berkaitan dengan kelima aspek STEAM akan memenuhi dan mempermudah pemahaman konteks soal dengan permainan gim untuk anak-anakKata kunci: asesmen numerasi, gim, STEAM.